Study on the Translation of Classical Allusions in Xi Jinping: The Governance of China Ⅳ from the Perspective of Eco-Translatology - Deng, Xule (International Journal of Social Sciences and Public Administration, 2025)
As China’s international standing ascends, the significance of translating political texts, particularly those involving classical allusions, becomes increasingly prominent. This translation process necessitates a delicate balance of linguistic transformation, cultural adaptation, and communicative efficacy. Drawing upon the framework of Eco-Translatology, this study examines the translator’s adaptive transformations in terms of linguistic, cultural, and communicative dimensions, using classical allusions in Volume IV of Xi Jinping: The Governance of China as illustrative examples. The objective of this research is to refine the analytical perspectives within political text translation studies. Through methodologies such as literature review and case studies, it explores the translator’s adaptive selections and translation strategies, aiming to achieve optimal translation outcomes. The findings reveal that Eco-Translatology facilitates the translator in maintaining a harmonious equilibrium between the original text’s literary value, political connotations, and the target audience’s cultural backdrop, thereby enhancing China’s international voice and shaping a favorable national image. This study contributes positively to the overseas dissemination of Chinese cultural ideas.